Impact of fiscal spending, financial inclusion on financial stability - Duan, Chengyonghui; Soh, Wei Ni (Elsevier, 2024)
The existing literature requires further comprehensive study on the relationship among fiscal expenditure, financial inclusion, and financial stability. This empirical study analyzes the impact of fiscal expenditure and financial inclusion on financial stability using panel data from 31 Chinese provinces (autonomous regions and municipalities directly under the central government) from 2011 to 2022. The study findings suggest that fiscal expenditures, financial inclusion, and technological development all improve financial stability. This study serves as a reference for designing fiscal expenditure measures and improving financial stability in the region.